The Influence Of Consumer Reviews And Indonesian National Team Brand Ambassadors On Purchase Intention For Le Minerale Products - Stevira Andien Razika; Dorothy Rouly Haratua Pandjaitan (Cita konsultindo, 2026)
The competition in the bottled water industry (AMDK) in Indonesia is increasingly intensifying along with the development of information technology and changes in consumer behavior in seeking product references. Consumers today tend to consider customer reviews and the influence of public figures before making a purchase. Le Minerale, as one of the bottled water brands in Indonesia, utilizes marketing strategies thru consumer reviews and collaboration with the Indonesian National Team as Brand Ambassadors to enhance consumer purchase intention. This study aims to determine the influence of consumer reviews and the Indonesian National Team Brand Ambassador on the purchase intention of Le Minerale products. This research employs a quantitative approach with data collection techniques thru questionnaires distributed to 120 respondents using the non-probability sampling method with purposive sampling technique. Data analysis is conducted using multiple linear regression and hypothesis testing both partially (t-test) and simultaneously (F-test). The research results show that consumer reviews have a positive and significant effect on the purchase intention of Le Minerale products. The Indonesian National Team Brand Ambassador also has a positive and significant effect on the purchase intention of Le Minerale products. Simultaneously, consumer reviews and the Indonesian National Team Brand Ambassador have a significant effect on the purchase intention of Le Minerale products.